Consumption attachments of Brazilian fans of the National Football League: A netnography on Twitter interactions - Bruno Melo Moura; André Luiz Maranh\~ao de Souza-Le\~ao (Innovation & Management Review, 2020)
Purpose - The National Football League (NFL), the most lucrative sports league in the world, has its second largest foreign audience in Brazil. Its Brazilian broadcasts stimulate the audience to extrapolate television reception and interact through a social media platform, seeking to integrate a collective consumption. Thus, attachments are established between consumers and league. Based on this, this study aims to analyze how the interaction in social media of the Brazilian NFL audience, during the transmissions of its games, results in consumption attachments. Design/methodology/approach The method undertaken was Netnography, commonly used to investigate cultural practices occurring in online environments. The research corpus consisted of messages posted on Twitterhashtags created by the ESPN Brazil channels to reverberate its broadcasts of the league between 2016-2017 and 2017-2018 seasons. Findings The findings of this study indicate that Brazilian audience interaction in social media establishes consumer attachment with the NFL by means of the brand elements and aspects of social life, mediated by the league. Research limitations/implications The research observed only the part of the Brazilian audience of the NFL that engages in the broadcasts of the games through social media. Practical implications The research of this study demonstrates how brands can use social media to enable social interactions that create or improve consumer attachments with them. Originality/value The study presents how a media brand imbricated in the American culture has been the target of attachment by Brazilian fans through social media interactions.
Keywords: 650; Attachment; Fans; Netnography; NFL; Prosumption